The Effectiveness of the Make a Match Method in Improving the Learning Outcomes of Islamic Religious Education in Elementary Schools - Supa'at Supa'at (Research Journal on Teacher Professional Development, 2025)
This research aims to improve the learning outcomes of grade II students of SD Negeri 2 Kendengsidialit on the material "Getting to Know Angels and Their Duties" through the application of the Make a Match method. Given the low achievement of learning completeness in the pre-cycle, classroom action research (PTK) was carried out for three cycles with a qualitative approach that integrated quantitative and qualitative data. The subjects of the study were 27 grade II students, with data collection techniques including participant observation—conducted by teachers as researchers and collaborators—as well as learning outcome tests at the end of each cycle. Quantitative data analysis is focused on calculating the average score and percentage of learning completeness, while qualitative data is analyzed through reduction, categorization, presentation, interpretation, and conclusion. The results showed a significant increase: in the pre-cycle, the average score was only 58.28 with a completeness of 11.43%; increased to 66.14 (45.71% completeness) in cycle I, 74.71 (65.71%) in cycle II, and reached 89.85 (100% completeness) in cycle III. These findings prove that  the Make a Match  method is effective in improving student learning outcomes in the teaching material. This research makes an original contribution in the form of innovative application of active learning methods in the context of Islamic religious education in elementary schools, while enriching the study of learning strategies that are responsive to the characteristics of early childhood students.